2009
DOI: 10.1021/jf902838b
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Composition and Antioxidant Capacity of Extruded Cranberry Pomace

Abstract: Cranberry pomace was mixed with corn starch in various ratios (30:70, 40:60, 50:50 pomace/corn starch DW) and extruded using a twin-screw extruder at three temperatures (150, 170, 190 degrees C) and two screw speeds (150, 200 rpm). Changes in the anthocyanin, flavonol, and procyanidin contents due to extrusion were determined by HPLC. Antioxidant capacity of the extrudates was determined using oxygen radical absorbance capacity (ORAC). Anthocyanin retention was dependent upon barrel temperature and percent pom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 38 publications
8
63
1
2
Order By: Relevance
“…The higher temperature possibly allowed for the release of phenolic and flavonoid compounds along with other constitutes like vitamin E present in sunflower seeds. These finding are similar to the findings of White et al (2009), who reported an increase in flavonoid content of cranberry pomace with an increase in extraction temperature. There results also revealed higher ORAC values of cranberry extracts (170 and 190°C) compared to whole cranberries.…”
Section: Enzymatic Activitiessupporting
confidence: 92%
“…The higher temperature possibly allowed for the release of phenolic and flavonoid compounds along with other constitutes like vitamin E present in sunflower seeds. These finding are similar to the findings of White et al (2009), who reported an increase in flavonoid content of cranberry pomace with an increase in extraction temperature. There results also revealed higher ORAC values of cranberry extracts (170 and 190°C) compared to whole cranberries.…”
Section: Enzymatic Activitiessupporting
confidence: 92%
“…The increase of antioxidant activity upon thermal treatment has been reported in past for tomato products (Dewanto et al 2002;Nicoli et al 1997). The increasing effect of extrusion temperature on antioxidant activity (determined with the ORAC method) has been found for twin screw extruded starch-cranberry pomace products processed at a temperature range between 150 and 190°C (White et al 2009). …”
Section: Antioxidant Activity Of Extrudatesmentioning
confidence: 85%
“…Previous data also showed that cranberry derived procyanidins had an additive antihyperglycemic effect in the presence of a low insulin dose (unpublished data). Furthermore, data have shown that extrusion processing of fruit byproducts, such as blueberry pomace, CBP, grape pomace, sorghum bran, and grape seeds can enhance the low molecular weight procyanidins that are bioavailable probably at the expense of some of their large molecular weight counterparts that are not readily absorbed (Gu et al, 2008;Khanal et al, 2009a,b;White et al, 2010). The objective of this study was to investigate the effect of feeding CBP on different metabolic characteristics associated with metabolic syndrome in high fructose fed growing rats.…”
Section: Introductionmentioning
confidence: 99%